Penerapan Metode Fun Learning dalam Pembelajaran Pendidikan Agama Islam pada Anak Usia Dini (Studi Kasus di PAUD Ummatan Wasathon Kota Serang) - Sanin Sudrajat; Munawaroh Munawaroh; Saepudin Saepudin; Hanafi Hanafi (Departement of Mathematics Education, 2024)
This research was carried out at the Ummatan Wasathon Kasemen PAUD, Serang City, Banten Province, which is expected to be used as a reference or study material in increasing knowledge in the field of education, especially Islamic Religious Education. This research aims to determine the application of the Fun Learning method in learning Islamic Religious Education in early childhood which is related to planning, implementation and evaluation of learning. The method used in this research is a descriptive analysis method with a qualitative approach through observation, interviews and documentation. In this research, the subjects were all students at PAUD Ummatan Wasathon Kasemen Serang City aged 3-6 years. Data was obtained by researchers through participant observation of classroom learning using observation guidelines which include aspects of opening activities, core activities, closing activities, and the learning environment. Researchers also conducted interviews and documentation to support the required data. Interviews were conducted with the school principal and 2 (two) teacher representatives based on predetermined interview guidelines. The results of this research show that the application of the Fun Learning method in learning Islamic Religious Education in early childhood which is related to planning, implementation and evaluation of learning has been carried out well with various efforts made by educators at PAUD Ummatan Wasathon Kasemen Serang City. However, there are still several things that need to be improved, such as making more focused learning plans, implementing reflection activities at the end of learning and providing facilities and infrastructure as learning resources and media so that learning can take place in a fun way and achieve educational goals.